Dietary fibre supplementation in late gestation modulates gut microbiota and improves reproductive performance and colostrum quality in sows - Cong, Guanglei; Liu, Chunxue; Xia, Shuangshuang; Li, Junbo; Hung, Ifen (Frontiers in Microbiology, 2025)
IntroductionDietary fibre in late gestation may affect sow physiology, colostrum quality, gut microbiota, and piglet performance. This study examined whether increasing fibre levels enhances sow health and reproductive outcomes.MethodsForty pregnant Landrace × Yorkshire sows (parity 2 or 4) were allocated to either a low-fibre (LF, 5.2%) or high-fibre (HF, 7.7%) diet from day 85 of gestation until parturition, after which all sows received a common lactation diet. Sow performance, constipation, nutrient digestibility, colostrum quality, cord blood parameters, and gut microbiota profiles were assessed. Piglet growth performance was recorded until weaning. Correlation analyses were conducted to examine associations between bacterial taxa and physiological indicators.ResultsHF sows showed improved piglet vitality (p < 0.05), higher faecal scores, and lower constipation rates (p < 0.05). Colostrum protein, total solids, IgA, and IgM concentrations were increased in HF sows (p < 0.05). Cord blood glucose and IL-10 were reduced, whereas eNOS was elevated (p < 0.05). Digestibility of crude fibre, ADF, and NDF increased, while protein digestibility decreased (p < 0.05). Gut microbiota analysis indicated increased abundances of Lactobacillus, Lachnospiraceae_XPB1014_group, and Methanobrevibacter, and decreased Treponema, Prevotellaceae_UCG-001, and Escherichia-Shigella. Piglets from HF sows exhibited greater average daily gain and weaning weight (p < 0.05). Beneficial associations were observed for Lactobacillus, Terrisporobacter, and Lachnospiraceae_XPB1014_group with reproductive traits; Phascolarctobacterium and X-Eubacterium_ruminantium_group correlated with piglet growth; while Treponema and Rikenellaceae_RC9_gut_group were negatively associated with constipation.DiscussionHigher dietary fibre in late gestation improved gastrointestinal function, colostrum quality, and piglet growth, likely through enhanced fibre digestibility and favourable modulation of gut microbiota. These findings support increased fibre supplementation to optimise sow and piglet health.